COMMUNITY SERVICE ACTIVITIES DIGITAL LITERACY TRAINING AND COMPANY FOR ORGANIZATIONAL CHILDREN MIFTAHUL JANNAH'S CARE - Rico Nur Ilham; Likdanawati; Hamdiah; Sutriani; Irada Sinta (International Review of Practical Innovation, Technology and Green Energy (IRPITAGE), 2023)
An orphanage is a place where underage children and the poor are placed in order to get a better life. With funding from donors who come from various people and various circles. So that not a few asyhan orphanage foundations are increasingly developing in terms of facilities, curriculum, business entities, etc. Due to the large number of donations that have come in, residents of the orphanage foundation sometimes misinterpret donations. So that there are many opportunities to take advantage of the conditions in the foundation to get better donations. Seen from the foundation's own foster children, who interpret donations when they are in their position in the foundation. As well as what impact is felt either directly or indirectly from the donation. The joint iftar event has become part of the holy month of Ramadan in this country. Iftar together is a routine agenda held by various groups, extended families, and an organization. Iftar together is not just eating together, but also used as a moment of hospitality and others.